Solubility of dicarbohydrazide bis[3-(5-nitroimino-1, 2, 4-triazole)] in common pure solvents and binary solvents at different temperatures. Issue 11 (13th November 2019) - Ren, Jianrong; Chen, Dong; Yu, Yanwu; Li, Hongzhen
Abstract : The solubility of dicarbohydrazide bis[3-(5-nitroimino-1, 2, 4-triazole)] (DCBNT) was first measured under the different pure solvents and binary solvents by the dynamic method over the temperature range of 290–360 K at atmospheric pressure. Results in all the solvents were positively correlated with temperature, namely increased with increasing temperature. The experiment data were correlated by the Apelblat equation, the Yaws equation and the polynomial equation. The conclusion showed that these three models all agreed well with the experimental data. Simultaneously, the dissolution enthalpy, dissolution entropy and Gibbs free energy of DCBNT in different solvents were calculated from the solubility data by using the Apelblat model. The results indicate that the dissolution process of DCBNT in these solvents is driven by entropy, which provides theoretical guidance for further research on the crystallization of DCBNT.